2002
DOI: 10.1046/j.1365-313x.2002.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a ‘unigene’ cDNA clone set by oligonucleotide fingerprinting allows access to 25 000 potential sugar beet genes

Abstract: SummaryAccess to the complete gene inventory of an organism is crucial to understanding physiological processes like development, differentiation, pathogenesis, or adaptation to the environment. Transcripts from many active genes are present at low copy numbers. Therefore, procedures that rely on random EST sequencing or on normalisation and subtraction methods have to produce massively redundant data to get access to low-abundance genes. Here, we present an improved oligonucleotide fingerprinting (ofp) approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…ESTs (21 321) representing 13 618 genes have been cloned from sugar beet (3 February 2005 release, http://compbio. dfci.harvard.edu/tgi/cgi-bin/tgi/gimain.pl?gudb=beet; Herwig et al, 2002;Bellin et al, 2007). There are 26 870 ESTs deposited in the GenBank (accessed on 13 November 2007), of which about 20% are estimated to represent defence, signal transduction and secondary product synthetic genes.…”
Section: Development Of Transgenic Technologymentioning
confidence: 99%
“…ESTs (21 321) representing 13 618 genes have been cloned from sugar beet (3 February 2005 release, http://compbio. dfci.harvard.edu/tgi/cgi-bin/tgi/gimain.pl?gudb=beet; Herwig et al, 2002;Bellin et al, 2007). There are 26 870 ESTs deposited in the GenBank (accessed on 13 November 2007), of which about 20% are estimated to represent defence, signal transduction and secondary product synthetic genes.…”
Section: Development Of Transgenic Technologymentioning
confidence: 99%
“…In a classical protocol of oligofingerprinting, PCR products are spotted on the nylon membrane and hybridized with radioactively labeled oligoprobes [18]. The method has been further modified by using fluorescence detection and application of PNA-modified oligoprobes [19].…”
Section: Model Verification -The Example Of Oligofingerprintingmentioning
confidence: 99%
“…It has been shown that reduction of the probe length results in a reduced number of hybridizations necessary for production of the unique fingerprint. For example, only 50 7-mer probes are theoretically required to deliver the same sequence information on particular DNA clones, whereas application of the 8-mer probes requires using 220 oligodeoxynucleotides [18]. Reduction of the number of hybridizations results, in turn, in a drastic reduction of costs in terms of reagents and time consumption.…”
Section: Model Verification -The Example Of Oligofingerprintingmentioning
confidence: 99%
“…A total of 107,283 clones were simultaneously analyzed by ONF as described earlier (Meier-Ewert et al 1998;Herwig et al 1999Herwig et al , 2002Poustka et al 1999;Clark et al 2001). To prevent overclustering by ONF, the clustering stringency was trained on the real representation of the cDNA clones representing 30 different genes, whose representation in the libraries was determined by backhybridization to the macroarrays of the used libraries.…”
Section: Normalization Est Sequencing and Clusteringmentioning
confidence: 99%